Stage-Dependent Mineral Element Dynamics in ‘Junzao’ Jujube: Ionic Homeostasis and Selective Transport Under Graduated Saline-Alkali Stress - Ze Yuan; Xiaofeng Zhou; Yuyang Zhang; Yan Wang; Haoyu Yan; Wu Sun; Min Yan; Cuiyun Wu (Horticulturae)
Plants dynamically regulate ions in the tree to defend against abiotic stresses such as drought and saline-alkali, However, it is not clear how ‘Junzao’ jujube regulates ions to maintain a normal life cycle under saline-alkali stress. Therefore, in this study, the roots of 10-year old steer jujube trees were watered using a saline and alkaline gradient solution simulating the main salt (NaCl) and alkali (NaHCO3) of Aral with NaCl:NaHCO3 = 3:1 gradient of 0, 60, 180, and 300 mM, and three jujube trees with uniform growth were taken as samples in each treatment plot, and the ion contents of potassium (K), sodium (Na), calcium (Ca), magnesium (Mg), iron (Fe), manganese (Mn), zinc (Zn) and carbon (C) in each organ of the fruit at the dot red period (S1) and full-red period (S2) were determined, in order to elucidate the relationship between physiological adaptation mechanisms of saline-alkali tolerance and the characteristics of mineral nutrient uptake and utilisation in jujube fruit. The results showed that under saline-alkali stress, Na was stored in large quantities in the roots, Ca and Mg in the perennial branches at S1, Na and Fe in the leaves at S2, and K, Mg and Mn in the perennial branches. There was no significant difference in the distribution of C content in various organs of ‘Junzao’. Compared with CK (0 mM), under salinity stress, the K content in the leaves was significantly reduced at S1 and S2, and the K/Na ratios remained > 1.0. At S2, under medium and high concentrations of saline-alkali stress (180–300 mM), the K/Na is less than 1, and the ionic homeostasis was disrupted, and the leaves die and fall off, and the Na is excreted from the body. The selective transport coefficients SK/Na, SCa/Na and SMg/Na from root to leaf showed a downward trend at S1, but still maintained positive transport capacity. At S2, this stage is close to leaf fall, the nutrient transport coefficient is less than 1, and a large amount of nutrients are returned to the perennial branches and roots occurred. These results indicated that the mechanism of nutrient regulation and salt tolerance in jujube trees was different at different growth stages.